Direct Nano‐Synthesis Methods Notably Benefit Mg‐Battery Cathode Performance. Issue 5 (25th February 2020) - Blanc, Lauren E.; Sun, Xiaoqi; Shyamsunder, Abhinandan; Duffort, Victor; Nazar, Linda F.
Abstract: Rechargeable magnesium batteries are promising candidates for next‐generation electrochemical energy storage, but their development is severely hindered by sluggish solid‐state diffusion and significant desolvation penalties of the divalent cation. Studies suggest that nano‐sized electrode materials alleviate these issues by shortening diffusion lengths and increasing electrode/electrolyte interaction. Here, the effect of particle size and synthetic methodology on the electrochemical performance of four sulfide cathode materials in Mg batteries is investigated: layered TiS2, CuS, spinel Ti2 S4, and CuCo2 S4 . In these sulfide hosts, the direct preparation of nano‐dimensional crystallites is critical to activate or improve electrochemistry. Even promising cathode materials can appear electrochemically inert when micron‐sized particles are investigated (e.g., CuCo2 S4 ), and mechanical milling leads to surface degradation of active material which severely limits performance. However, nano‐sized CuCo2 S4 prepared directly reaches a capacity nearly double that of ball‐milled material and delivers 350 mAh g −1 at 60 °C. This work provides synthetic considerations which may be crucial in the discovery and design of novel Mg cathode materials, so that promising candidates are not overlooked. By extension, in oxide materials where Mg 2+ diffusion is expected to be much more sluggish, this factor is anticipated to be even more important when screening for new hosts. Abstract : The method of preparation of nano‐sized electrode materials plays a key role in their observed electrochemistry, where optimal performance is obtained through direct nano‐synthesis techniques rather than mechanical milling methods. Developing such nanosynthetic routes can lead to the discovery of novel Mg cathode materials—such as CuCo2 S4 —that might otherwise be overlooked when screening for new candidates.